Population pharmacokinetics of ethanamizuril in normal and coccidiosis‐infected chickens through ultra‐performance liquid chromatography–Tandem Mass Spectrometry. Issue 4 (6th May 2020) - Wang, Xiaoyang; Zhang, Keyu; Wang, Mi; Zhang, Lifang; Fei, Chenzhong; Wang, Chunmei; Liu, Yingchun; Xue, Feiqun; Hang, Taijun
Abstract: Ethanamizuril is a new triazine compound that shows potential for application in novel anticoccidial treatment. In this study, a pharmacokinetic model of ethanamizuril was established on the basis of the blood concentration of 81 experimental animals. The final model showed that ethanamizuril was distributed as a two‐compartment model with first‐order absorption after oral administration in chickens. Its clearance rate and volumn of central compartment distribution ( V c ) were affected by age and body weight, and volumn of central compartment distribution ( V c ) and volume of peripheral compartment distribution( V p ) were influenced by weight and infection. External verification revealed that the model had good prediction accuracy and stability.